Relationship between Fecal Content of Fatty Acids and Cyclooxygenase mRNA Expression and Fatty Acid Composition in Duodenal Biopsies, Serum Lipoproteins, and Dietary Fat in Colectomized Familial Adenomatous Polyposis Patients - K. Almendingen; A. T. Høstmark; L. N. Larsen; O. Fausa; J. Bratlie; L. Aabakken (Journal of Nutrition and Metabolism)
A few familial adenomatous polyposis studies have focused upon faecal sterols and bile acids but none has analysed the fecal content of fatty acids. We report here findings of an observational study on 29 colectomized familial adenomatous polyposis patients that describe the fecal content of fatty acids, and relate this to the proportions of fatty acids and levels of cyclooxygenase mRNA expression in duodenal biopsies, levels of serum lipoproteins, and diet. In the ileostomy group separately (n=12), the fecal content of arachidonic acid was correlated negatively to the proportions of eicosapentaenoic acid and docosahexaenoic acid in duodenal biopsies. Total serum-cholesterol was negatively correlated to the fecal content of saturates and monounsaturates. The fecal palmitoleic acid/palmitic acid ratio was positively correlated to the levels of cyclooxygease-2 expression in duodenal biopsies.In the ileal-pouch-anal anastomosis group separately (n=17), significant correlations were found between the fecal contents of oleic acid, linoleic acid, and alpha-linolenic acid, and the proportions of myristic acid, oleic acid and eicosaenoic acid in duodenal biopsies. Dietary monounsaturates were positively correlated to different fecal fatty acids. Future studies should focus on molecular mechanisms relevant to fatty acid metabolism, inflammation, and angiogenesis, in addition to nutrition.